2015
DOI: 10.1080/09168451.2015.1038213
|View full text |Cite
|
Sign up to set email alerts
|

Development of LNA oligonucleotide–PCR clamping technique in investigating the community structures of plant-associated bacteria

Abstract: Simultaneous extraction of plant organelle (mitochondria and plastid) genes during the DNA extraction step is major limitation in investigating the community structures of plant-associated bacteria. Although locked nucleic acid (LNA) oligonucleotides was designed to selectively amplify the bacterial small subunit rRNA genes by applying the PCR clamping technique, those for plastids were applicable only for particular plants, while those for mitochondria were available throughout most plants. To widen the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To improve amplification efficiency, three new forward primers and one new reverse primer were designed at positions to compete with LNA oligonucleotides specific for plant organelle (mitochondria and plastid) SSU rRNA genes. The LNA oligonucleotides used herein were described in our previous studies ( 13 , 14 ), and their sequences and properties were shown in supplementary Table S2 . The amplification efficiencies of the newly designed primer sets were compared for their respective PCR products prepared from the roots of rice, potato, soybean, and turnip green.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve amplification efficiency, three new forward primers and one new reverse primer were designed at positions to compete with LNA oligonucleotides specific for plant organelle (mitochondria and plastid) SSU rRNA genes. The LNA oligonucleotides used herein were described in our previous studies ( 13 , 14 ), and their sequences and properties were shown in supplementary Table S2 . The amplification efficiencies of the newly designed primer sets were compared for their respective PCR products prepared from the roots of rice, potato, soybean, and turnip green.…”
mentioning
confidence: 99%
“…2) were cultivated in potted soil. Cultivation procedures were the same as those described by Ikenaga et al ( 13 , 14 ). The roots of rice and soybean were collected at the seedling stage, while those of potato and turnip green were collected at the harvest stage.…”
mentioning
confidence: 99%
“…We have developed an LNA oligonucleotide–PCR clamping technique in order to investigate the community structures of plant–associated bacteria ( 20 , 21 , 22 ). This technique has enabled the PCR amplification of bacterial SSU rRNA genes, while inhibiting the amplification of host plant organelle (mitochondria and plastid) genes.…”
mentioning
confidence: 99%